2019
DOI: 10.19184/nlj.v4i1.8628
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Education Giving on The Parent's Behavior About Growth Stimulation in Children with Stunting

Abstract: Stunting (short body) is a very short body state that goes beyond 2 SD below the median length or height of the population body which is an international reference. Stunting describes a lack of nutrition that has been going on for a long time and requires time for children to develop and recover. A number of studies show a link between stunting with poor motor and mental development in early childhood, and poor cognitive achievement and school achievement in late childhood. In Sleman Regency in 2014 the stunti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
0
9
0
2
Order By: Relevance
“…Wuryanti et al performed nutrition educational counseling in Kemayoran,Central Jakarta, reported that maternal knowledge significantly increased after the counseling (Wuryanti dkk, 2019). Several studies also showed the increment of parental knowledge after educational counseling was performed audio-visually and active question-answer sessions (Hati & Pratiwi, 2019). This activity is held in the form of educational counseling and leaflet distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Wuryanti et al performed nutrition educational counseling in Kemayoran,Central Jakarta, reported that maternal knowledge significantly increased after the counseling (Wuryanti dkk, 2019). Several studies also showed the increment of parental knowledge after educational counseling was performed audio-visually and active question-answer sessions (Hati & Pratiwi, 2019). This activity is held in the form of educational counseling and leaflet distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the training of health cadres in early detection of nutritional disorders also showed an increase in knowledge and skills. The impact is that the health cadres have shown improvements in making referrals for nutritional disorders for children under five, while mentoring by cadres has a positive impact on nutrition health services for children under five (Hati & Pratiwi 2019).…”
Section: Respondents' Level Of Knowledgementioning
confidence: 99%
“…Various potential resources in the family that are utilised properly will help overcome existing problems more effectively than using other resources that are not necessarily owned [2]. The high incidence of stunting and the suboptimal level of public health are basically influenced by environmental conditions, community behaviour, health services and genetics [3]. The family as the closest resource still cannot be maximised in carrying out its functions, especially in preventing and handling stunting.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition-sensitive interventions are efforts to deal with stunting by targeting the general public including the family environment, which contributes to 70% of stunting interventions [3]. Nutrition-sensitive interventions include 12 things that can be done by families and communities to treat stunting in toddlers.…”
Section: Introductionmentioning
confidence: 99%